Desenvolvimento regional ancorado na agricultura familiar: a tecnologia em prol de uma gestão de qualidade - Wandermurem, Romildo Ferreira (2023)
The agribusiness sector directly linked to family farming that strongly impacts the Brazilian economy, whose activities are carried out with a predominance of family labor and the country's economic development. In view of the importance of agricultural and economic production in western Paraná, this research aimed to contribute directly to the family farmer, through the management of the rural property, providing better decision-making regarding profitability. In which the use of technology was applied and implemented through an electronic spreadsheet containing symbols and easy-to-understand writing, which allowed mapping both in the management and in the georeferencing of small properties linked to family farming, pointing out technical and economic coefficients related to management, in order to predict the financial flow of products/quantities and sales/profit. However, inserting data for a better use of the land, who produces and manages products and the consumer market, whose areas are polyculture that diversified between grain, vegetable, fruit and pig production, poultry, cattle as well as derivatives. The research took place via technical procedures for field research via interviews and document analysis, highlighting the importance of technology, through management that provided for subsidizing possible crop exchanges for productive continuity in rural agricultural units, seeking a better development of family farming, validating and varying the products that can meet the requirements of the consumer market. The area surveyed were six small properties in Sede Alvorada, Cascavel district in Oeste Paranaense, through technical visits and questionnaires, as well as a pilot project, places where the subdivision and/or lease of land has currently occurred due to disorganization in management. The aim of this research was to encourage and maintain small farmers on their properties, as well as social and technological equity for land use through technology. What proved to be satisfactory to those surveyed, as the numbers, when selected and shown, served as an incentive for the need to have real planning, as well as a better use of the land.